Fulfillment of Children's Post-Divorce Supporting Obligations from an Islamic Law Perspective in Polewali Mandar Regency - Sumiati; Agus Muchsin; Zainal Said; Sudirman L; M. Ali Rusdi (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
The rights of children after divorce, both in the Marriage Law and the Compilation of Islamic Law, are that children have the right to continue to receive maintenance, care and education from their parents. In terms of financing the maintenance and education of children after divorce, it is the responsibility of the father, which in the Compilation of Islamic Law is known as hadhanah living. This is a form of parental responsibility in carrying out their obligations for the realization of children's rights as regulated in Law Number 23 of 2002 concerning Child Protection. However, mothers also help in managing the household and maintaining the welfare and happiness of the family. Therefore, father and mother both have an important role in the family, and the integrity of both is highly expected in a family in order to achieve a happy family. This type of research is field research. According to Dedy Mulyana, field research is a type of research that studies phenomena in their natural environment. For this reason, primary data is data that comes from the field. So that the data obtained truly corresponds to the reality regarding the phenomena that exist at the research location. Based on the results of the interview with Mr Syamsul, he explained that he was still able to work but did not carry out his responsibilities regarding child support rights after divorce based on the results of court decision Number 65/Pdt.G/2023/PA.Pwl which sentenced the applicant to provide child support for 3 (three) children in the amount of Rp. 2,000,000 (two million rupiah) per month until the child is an adult or 21 years old with an additional 10% each year excluding education and health costs. Based on the results that the researcher has obtained, it can be concluded that the father's fulfillment of child support rights post-divorce in Polewali Mandar Regency based on the results of court decision Number 65/Pdt.G/2023/PA.Pwl has not been fully carried out by the father. This is caused by various factors, ranging from economic incompetence, indifference, to a lack of effective law enforcement mechanisms